Cystathionine β-synthase mediated PRRX2/IL-6/STAT3 inactivation suppresses Tregs infiltration and induces apoptosis to inhibit HCC carcinogenesis - Zhou, Yu-Fu; Song, Shu-Shu; Tian, Meng-Xin; Tang, Zheng; Wang, Han; Fang, Yuan; Qu, Wei-Feng; Jiang, Xi-Fei; Tao, Chen-Yang; Huang, Run; Zhou, Pei-Yun; Zhu, Shi-Guo; et al. (Journal for immunotherapy of cancer, 2021)
BackgroundHepatocellular carcinoma (HCC) is characterized by inflammation and immunopathogenesis. Accumulating evidence has shown that the cystathionine β-synthase/hydrogen sulfide (CBS/H2S) axis is involved in the regulation of inflammation. However, roles of CBS in HCC development and immune evasion have not been systematically investigated, and their underlying mechanisms remain elusive. Here, we investigated the roles of CBS in tumor cells and tumor microenvironment of HCC.Methods236 HCC samples were collected to detect the expression of CBS, cleaved Caspase-3 and paired related homeobox 2 (PRRX2) and the number of immune cells. HCC cell lines were employed to examine the effects of CBS on cellular viability, apoptosis and signaling in vitro. Cbs heterozygous knockout mice, C57BL/6 mice, nude mice and non-obese diabetic severe combined immunodeficiency mice were used to investigate the in vivo functions of CBS.ResultsDownregulation of CBS was observed in HCC, and low expression of CBS predicted poor prognosis in HCC patients. CBS overexpression dramatically promoted cellular apoptosis in vitro and inhibited tumor growth in vivo. Activation of the Cbs/H2S axis also reduced the abundance of tumor-infiltrating Tregs, while Cbs deficiency promoted Tregs-mediated immune evasion and boosted tumor growth in Cbs heterozygous knockout mice. Mechanistically, CBS facilitated the expression cleaved Caspase-3 in tumor cells, and on the other hand, suppressed Foxp3 expression in Tregs via inactivating IL-6/STAT3 pathway. As a transcription factor of IL-6, PRRX2 was reduced by CBS. Additionally, miR-24-3p was proven to be an upstream suppressor of CBS in HCC.ConclusionsOur results indicate the antitumor function of CBS in HCC by inactivation of the PRRX2/IL-6/STAT3 pathway, which may serve as a potential target for HCC clinical immunotherapy.